Newly-Detected Solitary Bony Lytic/Sclerotic Lesion with Soft Tissue Mass in a Previously Treated Case of High-Risk Medulloblastoma: Importance of Contemporary Pathology Techniques to Differentiate Second Malignant Neoplasm from Extra-Neuraxial Metastasis - Gupta Tejpal; Krishna Uday; Epari Sridhar; Kurkure Purna; Jalali Rakesh (Journal of Brain And Spinal Cancer, 2015)
Multi-modality therapy has led to significant improvement in outcomes for childhood medulloblastoma; however, long-term survivors have become more susceptible to late effects of therapy including induction of second malignant neoplasms and even remain at an increased risk of late relapses including extra-neuraxial metastases. A newly detected solitary lytic/sclerotic osseous lesion in a medulloblastoma survivor away from the radiation field poses considerable diagnostic challenge as it could represent either a second malignant neoplasm or extra-neuraxial metastasis. We report one such case highlighting the importance of contemporary pathology techniques as useful adjuncts to differentiate a second primary osseous Ewing’s sarcoma (ES)/primitive neuro-ectodermal tumor (PNET) from bony metastasis and review the pertinent literature on second malignant neoplasms and extra-neuraxial metastases in medulloblastoma. To the best of our knowledge, this is the first report of a molecularly confirmed second primary osseous ES/PNET in a survivor of childhood medulloblastoma.
Keywords: medulloblastoma